2016
DOI: 10.1002/adem.201500629
|View full text |Cite
|
Sign up to set email alerts
|

Fretting Corrosion Behavior of Additive Manufactured and Cryogenic‐Machined Ti6Al4V for Biomedical Applications

Abstract: Metal ion release, caused by synergistic effect of wear and corrosion, is one of the major concerns related to the prostheses lifetime. In this work, samples of additive manufactured Ti6Al4V are machined under dry cutting and cryogenic cooling conditions and their performances in terms of corrosion and fretting corrosion response are investigated. A wet and temperature-controlled apparatus equipped with an electro-chemical cell is designed and set-up in order to evaluate the fretting corrosion effect acting at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…33 [12,59]. For surface generation, conventional milling and drilling are commonly used in the production lines for polymer-composite machining [91,120], which, however, could introduce severe subsurface damage and high cutting forces [16,92,120]. An effective way to minimise these effects is to employ abrasive machining, e.g.…”
Section: Polymer Composite Cuttingmentioning
confidence: 99%
See 1 more Smart Citation
“…33 [12,59]. For surface generation, conventional milling and drilling are commonly used in the production lines for polymer-composite machining [91,120], which, however, could introduce severe subsurface damage and high cutting forces [16,92,120]. An effective way to minimise these effects is to employ abrasive machining, e.g.…”
Section: Polymer Composite Cuttingmentioning
confidence: 99%
“…60). Bruschi and co-workers reported in several investigations on the impact of machining parameters and cooling strategies on the wear behaviour [23,24] and tribocorrosion performance [16,17] of wrought and additive manufactured Ti6Al4V alloys for biomedical applications. Wear tests were performed using a cylinder-on-plate configuration in a wet and temperaturecontrolled saline environment (Fig.…”
Section: Corrosion Resistance and Tribocorrosion Performancementioning
confidence: 99%
“…Eqs. (1)- (5) suggest that dislocation density during deformation increases with higher shear strain and lower temperature. Consistent with this prediction, the apparent dislocation cell density in Ti-6Al-4V alloy subjected to asymmetric cryorolling was observed to be higher than that resulting from asymmetric rolling, and it is lowest in the alloy subjected to cold rolling with the same rolling reduction.…”
Section: Is a Technique That Combines Features Of Asymmetric Rolling mentioning
confidence: 99%
“…Cryogenic cooling allowed a reduction in the adhesive wear mechanism of Ti-6Al-4V used on the tool cutting surfaces [4]. Bertolini et al [5] found that cryogenic machining improves the corrosion and fretting corrosion resistance of Ti-6Al-4V alloy fabricated by additive manufacturing. Huang et al [6] used thermo-hydrogen processing to improve the mechanical strength of Ti-6Al-4V from 930 MPa to 1160 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic implants, in contrast to a transplant which are biological products, are humanmade products. The surface of implants which comes in contact with the live tissues, cells or blood should be essentially made of a biomedical metal such as titanium or titanium alloy for eradication of rejection or infection [2,21,22]. Titanium has acceptable mechanical properties and has been used for orthopedic implants, yet for still better performance titanium is alloyed with small amounts of aluminium and vanadium (Ti-6Al-4V), typically 6% and 4% respectively, by weight [3,23,24].…”
Section: Introductionmentioning
confidence: 99%